Spider silk: Mother Nature’s bio-superlens - Monk, J; Yan, B; Hawkins, N; Vollrath, F; Wang, Z (American Chemical Society, 2016)
It was recently discovered that transparent micro-spheres and cylinders can function as super-resolution lens (i.e superlens) to focus light beyond the diffraction limit. A number of high-resolution applications based on these lenses have been successfully demonstrated and span nanoscopy, imaging and spectroscopy. Fabrication of these superlenses, however, are often complex and require sophisticated engineering processes. Clearly an easier model candidate, such as a naturally occurring superlens, is highly desirable. Here, we report for the first time a biological superlens provided by Nature: the Minor Ampullate spider silk spun from the Nephila spider. This natural bio-superlens can distinctly resolve 100 nm features under a conventional white-light microscope with peak wavelength at 600 nm, attaining a resolution of λ/6 that is well beyond the classical limit. Thus our work opens a new door to develop biology-based optical systems that may provide a new solution to integrating optics in biological systems.